Accountability Agreements for Ontario Universities: The Balancing Character of a Policy Instrument - Díaz, Victoria (Revue Gouvernance / Governance Review, 2016)
This paper demonstrates how the choice of instrument facilitates acceptance of a new accountability requirement in the Ontario university sector as it helps balance the government’s need for control with the universities’ need for independence. The instrument, conceptualized as an agreement, embodies the negotiated character of the relationship between government and universities, and conveys the idea to different actors that their needs are met. Despite the promises of the instrument, when objectives are ambiguous, uncertainty is pervasive, and negotiation is limited, the increase in government control is minimized and the changes in university autonomy are negligible, thus suggesting that symbolic and rhetorical compliance may be the sustainable equilibrium between governments and governed. Nonetheless, some level of transformation is observed in the sector as the new tool contributes to strengthening priority alignment, highlighting the value of sharing stories, and increasing acceptance of reporting requirements.